Long noncoding RNAs in organogenesis: making the difference. Issue 6 (June 2015) - Grote, Phillip; Herrmann, Bernhard G
Highlights lncRNAs are important for lineage choice and differentiation processes. lncRNAs interact with chromatin and transcription control factors. lncRNAs are involved in fine-tuning gene regulatory networks. lncRNAs may have promoted the evolution of complex tissues and organs.